The Nontoxic Cholera B Subunit Is a Potent Adjuvant for Intradermal DC-Targeted Vaccination - Antonio-Herrera, Laura; Badillo-Godinez, Oscar; Medina-Contreras, Oscar; Tepale-Segura, Araceli; García-Lozano, Alberto; Gutierrez-Xicotencatl, Lourdes; Soldevila, Gloria; Esquivel-Guadarrama, Fernando R.; Idoyaga, Juliana; Bonifaz, Laura C. (Frontiers in Immunology, 2018)
CD4+ T cells are major players in the immune response against several diseases; including AIDS, leishmaniasis, tuberculosis, influenza and cancer. Their activation has been successfully achieved by administering antigen coupled with antibodies, against DC-specific receptors in combination with adjuvants. Unfortunately, most of the adjuvants used so far in experimental models are unsuitable for human use. Therefore, human DC-targeted vaccination awaits the description of potent, yet nontoxic adjuvants. The nontoxic cholera B subunit (CTB) can be safely used in humans and it has the potential to activate CD4+ T cell responses. However, it remains unclear whether CTB can promote DC activation and can act as an adjuvant for DC-targeted antigens. Here, we evaluated the CTB’s capacity to activate DCs and CD4+ T cell responses, and to generate long-lasting protective immunity. Intradermal (i.d.) administration of CTB promoted late and prolonged activation and accumulation of skin and lymphoid-resident DCs. When CTB was co-administered with anti-DEC205-OVA, it promoted CD4+ T cell expansion, differentiation, and infiltration to peripheral nonlymphoid tissues, i.e., the skin, lungs and intestine. Indeed, CTB promoted a polyfunctional CD4+ T cell response, including the priming of Th1 and Th17 cells, as well as resident memory T (RM) cell differentiation in peripheral nonlymphoid tissues. It is worth noting that CTB together with a DC-targeted antigen promoted local and systemic protection against experimental melanoma and murine rotavirus. We conclude that CTB administered i.d. can be used as an adjuvant to DC-targeted antigens for the induction of broad CD4+ T cell responses as well as for promoting long-lasting protective immunity.